2011
DOI: 10.1128/aem.02178-10
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Cell Wall Microenvironment in Expression of a Heterologous SpaP-S1 Fusion Protein by Streptococcus gordonii

Abstract: The charge density in the cell wall microenvironment of Gram-positive bacteria is believed to influence the expression of heterologous proteins. To test this, the expression of a SpaP-S1 fusion protein, consisting of the surface protein SpaP of Streptococcus mutans and a pertussis toxin S1 fragment, was studied in the live vaccine candidate bacterium Streptococcus gordonii. Results showed that the parent strain PM14 expressed very low levels of SpaP-S1. By comparison, the dlt mutant strain, which has a mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…A possible explanation is that the increased adherence is the result of non-specific interactions between the bacterium and host cell due to a change in cell surface charges. SspA and SspB are calcium-binding proteins (Duan et al, 1994) and in the absence of these two proteins, OB219 has a more negative cell surface charge than the parent strain (Davis et al, 2011). However, the interactions did not involve PAMPs and cellular receptors that lead to cytokine production.…”
Section: Discussionmentioning
confidence: 94%
“…A possible explanation is that the increased adherence is the result of non-specific interactions between the bacterium and host cell due to a change in cell surface charges. SspA and SspB are calcium-binding proteins (Duan et al, 1994) and in the absence of these two proteins, OB219 has a more negative cell surface charge than the parent strain (Davis et al, 2011). However, the interactions did not involve PAMPs and cellular receptors that lead to cytokine production.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, we found that the fluorescence signal of a surface displayed GFP‐SpaP fusion protein was reduced in the S. mutans strain lacking prsA . This result is consistent with observations that there was a positive correlation between the level of PrsA and the amount of a surface‐localized fusion protein consisting of S. mutans SpaP and the pertussis toxin S1 fragment following expression in the heterologous host S. gordonii (Davis et al ., ). Furthermore, the level of PrsA was found to be linearly proportional to the protein secretion rate in B. subtilis (Vitikainen et al ., ); whereas overproduction of PrsA could increase the stability of the amylase and the protective antigen from B. subtilis (Kontinen & Sarvas, ; Williams et al ., ; Vitikaninen et al ., ), and prevent degradation of proteins on the cell surface of L. lactis (Drouault et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Cells from BHIS cultures with OD 600 values of 0.2 were boiled in SDS-PAGE sample buffer (250 mM Tris-HCl [pH 6.8], 2% sodium dodecyl sulfate, 10% glycerol, 10% 2-mercaptoethanol, 0.01% bromphenol blue), and the protein extracts were electrophoresed on 12.5% SDS-PAGE gels. The proteins were transferred to nitrocellulose membranes (Bio-Rad Laboratories) using standard techniques (34), blocked with 5% skim milk, and reacted with either rabbit anti-HtrA (S. pneumoniae) antiserum (1:500 dilution; a gift from Jeffrey Weiser, University of Pennsylvania) (35) or mouse anti-PrsA antiserum (36). The membranes were then reacted with goat anti-rabbit IgG-alkaline phosphatase (1:30,000 dilution; Sigma-Aldrich) or goat anti-mouse IgG-alkaline phosphatase (1:30,000 dilution; Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%